Physical exercise and blood pressure control for hypertension in menopausal women - Iba Supra Saba; Irna Nursanti; Wati Jumaiyah; Dhea Natashia; Mira Rosmiatin (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Hypertension is one of the non-communicable diseases that is a concern throughout the world, including Indonesia. Hypertension occurs frequently in menopausal women, because at menopause there is a decrease in estrogen hormones, so there is a risk of suffering from hypertension. One of the non-pharmacological therapies to control blood pressure in menopausal women is aerobic exercise. Sejati intervention is aerobic exercise that can cause a decrease in heart rate, which will reduce cardiac output, which ultimately causes a decrease in blood pressure. Purpose: To see the effectiveness of Sejati intervention on blood pressure in menopausal women. Method: The research design used was a quasy experiment, namely with a pre-test and post-test research design with a control group. The number of samples in this study was 36 respondents with 18 respondents in the intervention group and 18 respondents in the control group. The inclusion criteria in this study were menopausal women with hypertension who have blood pressure ≥140/90 mmHg and the exclusion criteria of this study were respondents with comorbidities. The statistical analysis used in this study was a linear regression test. Results: There was the effect of sejati intervention on blood pressure in menopausal women with hypertension at the Bojonggambir Health Center, Tasikmalaya Regency with a p value of 0.000 < α 0.05. Conclusion: The sejati intervention has an effect on reducing blood pressure in menopausal women. Suggestion: This research can be used as a reference material for further research.